STRATEGI REALISASI USULAN HASIL MUSRENBANG DALAM RKPD DI KABUPATEN ACEH SELATAN - sella rozatul mukminah (Cattleya Darmaya Fortuna, 2022)
The purpose of this study was to identify the problems causing the lack of effectiveness of the implementation of the Musrenbang that was carried out and to determine alternative improvements to the realization of the results of the Musrenbang in South Aceh District. This research uses an approach approach through descriptive analysis method. The data collection technique was through interviews with 10 key informants from local communities, Bappeda management, village administrators, and sub-district administrators. The results obtained from the causes of the realization of the Musrenbang not running properly are that the community does not know which problems are more precise with their regional problems, the level of community attendance is still low and the lack of confidence in the local government. Alternative strategic programs that can be implemented are providing guidance and understanding to the community through the provision of seminars and outreach for the community, implementation of the E-musrenbang-based implementation program and monthly or annual meeting activities as an evaluation of the proposals given by the community.